New approach to desensitization in solid organ transplantation-imlifidase - Durlik, Magdalena (Frontiers in Transplantation, 2022)
The IgG-degrading enzyme derived from Streptococcus pyogenes is a recombinant cysteine protease of S. pyogenes produced in Escherichia coli that cleaves all four human subclasses of IgG with strict specificity. The proteolytic activity on IgG molecules prevents the occurrence of IgG-mediated antibody-dependent, cellular cytotoxicity and complement-mediated cytotoxicity, two processes that are critical for antibody rejection. The results from phase II studies demonstrated that desensitization with imlifidase represents a therapeutic strategy that can operationalize desensitization, allowing life-saving transplants from DD and LD to proceed in highly sensitized kidney transplant candidates with low risk of hyperacute rejection. Imlifdase received conditional approval on 26 August 2020 in the EU for desensitization treatment of highly sensitized adult kidney transplant patients with positive crossmatch against an available deceased donor.